What Undermines Aid's Impact on Growth? - Subramanian, Arvind; Rajan, Raghuram (Washington, D.C. : International Monetary Fund, 2005)
We examine one of the most important and intriguing puzzles in economics: why it is so hard to find a robust effect of aid on the long-term growth of poor countries, even those with good policies. We look for a possible offset to the beneficial effects of aid, using a methodology that exploits both cross-country and within-country variation. We find that aid inflows have systematic adverse effects on a country's competitiveness, as reflected in a decline in the share of labor intensive and tradable industries in the manufacturing sector. We find evidence suggesting that these effects stem from the real exchange rate overvaluation caused by aid inflows. By contrast, private-to-private flows like remittances do not seem to create these adverse effects. We offer an explanation why and conclude with a discussion of the policy implications of these findings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet